2012
DOI: 10.5770/cgj.15.27
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in Older Adults Using Pre-hospital Care and the Emergency Department: A Narrative Review

Abstract: BackgroundOlder adults use more health-care services per capita than younger age groups and the older adult population varies greatly in its needs. Evidence suggests that there is a critical distinction between relative frailty and fitness in older adults. Here, we review how frailty is described in the pre-hospital literature and in the broader emergency medicine literature.MethodsPubMed was used as the primary database, but was augmented by searches of CINAHL and EMBASE. Articles were included if they focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
(79 reference statements)
1
33
0
Order By: Relevance
“…(32) Additionally, current work practices, guidelines and protocols are biased towards assessment and management of critically ill or injured patients, (32) and currently offer little direction in assessment of frailty as part of routine clinical assessment. (10) Consequently, there is a risk that paramedics' clinical decision making relating to a frail older adult, regardless of their living environment, is based on little objective data and insufficient practice guidelines. (10) Integration into current systems and ease of application of any tool in the clinical environment is an important consideration in paramedic practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(32) Additionally, current work practices, guidelines and protocols are biased towards assessment and management of critically ill or injured patients, (32) and currently offer little direction in assessment of frailty as part of routine clinical assessment. (10) Consequently, there is a risk that paramedics' clinical decision making relating to a frail older adult, regardless of their living environment, is based on little objective data and insufficient practice guidelines. (10) Integration into current systems and ease of application of any tool in the clinical environment is an important consideration in paramedic practice.…”
Section: Discussionmentioning
confidence: 99%
“…(2) In regards to ageing, recognition and risk stratification of older adults by degrees of frailty may prove more beneficial than age as a predictor of adverse outcomes. (2,10,11) While associated with disability, comorbidity and age, frailty is its own distinct and dynamic clinical entity. (2) Two predominant approaches of identifying frailty have emerged: the frailty phenotype (FP) (12) and the frailty index (FI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tools may be proxy markers of frailty. 33 General risk-screening tools have been evaluated in the ED, with the two most commonly studied being the Identification of Seniors at Risk (ISAR) 34 and Triage Risk Screening Tool (TRST) 35 . The ISAR is a self-or caregiver-completed, six-item measure administered during the ED visit, either upon early presentation or prior to discharge.…”
Section: Frailty: Screening and Assessmentmentioning
confidence: 99%
“…6 A recent systematic review incorporating 31 studies of frailty in persons aged 65 and older found a prevalence from 4.0 to 17.0% of frailty, markedly increased in subjects older than 80. 19 Although the role of the components of frailty should be universal, it is possible that in the case of Mexico the prevalence of frailty may be influenced by other characteristics, such as inequality in health conditions, sociodemographics or genetic factors. 20 …”
Section: Declaration Of Conflict Of Interestsmentioning
confidence: 99%